2017
DOI: 10.23846/sr61158
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of agricultural certification schemes for improving socio-economic outcomes in low- and middle-income countries

Abstract: The International Initiative for Impact Evaluation (3ie) is an international grant-making NGO promoting evidence-informed development policies and programmes. We are the global leader in funding, producing and synthesising high-quality evidence of what works, how, why and at what cost. We believe that better and policy-relevant evidence will make development more effective and improve people's lives. 3ie systematic reviews 3ie systematic reviews examine available high-quality evidence on the effects of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…3ie publishes a series of Systematic Review Summary reports, which present review evidence structured around the theory of change, and focus more clearly on how the interventions themselves work and the reasons underlying heterogeneity in findings. Examples of these summaries are in Table 1 (De Buck et al 2017;Kristjansson et al 2016;Oya et al 2017;Snilstveit et al 2016;Stewart et al, 2016; 3. Keeping reviews up to date Systematic reviews need to be kept up to date.…”
Section: Fostering Learning By Using Programme Theory and Telling A Gmentioning
confidence: 99%
See 1 more Smart Citation
“…3ie publishes a series of Systematic Review Summary reports, which present review evidence structured around the theory of change, and focus more clearly on how the interventions themselves work and the reasons underlying heterogeneity in findings. Examples of these summaries are in Table 1 (De Buck et al 2017;Kristjansson et al 2016;Oya et al 2017;Snilstveit et al 2016;Stewart et al, 2016; 3. Keeping reviews up to date Systematic reviews need to be kept up to date.…”
Section: Fostering Learning By Using Programme Theory and Telling A Gmentioning
confidence: 99%
“…• Certification schemes are effective in raising prices and income from agriculture, but do not usually improve household income and wages (Oya et al 2017). Costs of implementing standards can prevent poor farmers joining the schemes, and training is often not oriented to the needs of smallholders and workers.…”
Section: Fostering Learning By Using Programme Theory and Telling A Gmentioning
confidence: 99%
“…This clearly hints at the complex way the target commodity is contextually embedded within livelihood strategies, and Oya et al . (: iii) further suggest the potential of ethnographic research to better ‘grasp the complexity of the local dynamics and explain successes and failures in more depth’. Our study addresses this challenge and contributes to the broader literature on assessing the impacts of sustainability programmes on rural livelihoods in the Global South.…”
Section: Sustainability Programmes Value Chains and Rural Livelihoodsmentioning
confidence: 99%
“…Another recent systematic review of the effectiveness of certification schemes for improving socioeconomic outcomes (Oya et al, 2017) found that, although there was evidence for improvements in intermediate outcomes (producer prices and agricultural income), there was less evidence of impacts on endpoint outcomes (wages, household income and assets). This clearly hints at the complex way the target commodity is contextually embedded within livelihood strategies, and Oya et al (2017: iii) further suggest the potential of ethnographic research to better 'grasp the complexity of the local dynamics and explain successes and failures in more depth'. Our study addresses this challenge and contributes to the broader literature on assessing the impacts of sustainability programmes on rural livelihoods in the Global South.…”
Section: Sustainability Programmes Value Chains and Rural Livelihoodsmentioning
confidence: 99%
See 1 more Smart Citation